Advances in cryptology – CRYPTO 2015. 35th Annual Cryptology Conference, Santa Barbara, CA, USA, August 16-20, 2015 : proceedings /: 35th Annual Cryptology Conference, Santa Barbara, CA, USA, August 16-20, 2015 : proceedings. Part I : ([2015]) - Unknown
No abstract available